Evolution of MAXI J1631–479 during the January 2019 outburst observed by INTEGRAL/IBIS. Issue 3 (11th January 2020) - Fiocchi, M; Onori, F; Bazzano, A; Bird, A J; Bodaghee, A; Charles, P A; Lepingwell, V A; Malizia, A; Masetti, N; Natalucci, L; Ubertini, P
ABSTRACT: We report on a recent bright outburst from the new X-ray binary transient MAXI J1631–479, observed in January 2019. In particular, we present the 30–200 keV analysis of spectral transitions observed with INTEGRAL /IBIS during its Galactic plane monitoring program. In the MAXI and BAT monitoring period, we observed two different spectral transitions between the high/soft and low/hard states. The INTEGRAL spectrum from data taken soon before the second transition is best described by a Comptonized thermal component with a temperature of kTe ∼ 30 keV and a high-luminosity value of L_2-200 keV3× 10^38 erg −1 (assuming a distance of 8 kpc). During the second transition, the source shows a hard, power-law spectrum. The lack of high energy cut-off indicates that the hard X-ray spectrum from MAXI J1631–479 is due to a non-thermal emission. Inverse Compton scattering of soft X-ray photons from a non-thermal or hybrid thermal/non-thermal electron distribution can explain the observed X-ray spectrum although a contribution to the hard X-ray emission from a jet cannot be determined at this stage. The outburst evolution in the hardness-intensity diagram, the spectral characteristics, and the rise and decay times of the outburst are suggesting that this system is a black hole candidate.